α-Melanocyte Stimulating Hormone in Critically Injured Trauma Patients - Todd, S. Rob (J Trauma, 2009)
BACKGROUND: α-Melanocyte stimulating hormone (α-MSH) is a neuropeptide which modulates inflammation. Prior studies have documented decreased α-MSH concentrations in patients with acute traumatic brain injury and subarachnoid hemorrhage. We hypothesized that α-MSH levels would be decreased in critically injured patients and that this would correlate with poor outcome. METHODS: We performed a retrospective review of prospectively collected data more than 12 months ending December 2005. α-MSH concentrations were measured in major torso trauma patients (excluding severe head injuries) who underwent standardized shock resuscitation. α-MSH concentrations were measured every 4 hours for the first 24 hours of intensive care unit admission and daily thereafter for hospital days 2 to 5. Controls were similarly aged, healthy volunteers. Outcomes measured included lengths of stay, infectious morbidity, and the incidence of multiple organ failure (MOF) and mortality. RESULTS: Fifty-one trauma patients were studied with a median age of 33 (22–54) years. Seventy-five percent were male and 82% sustained blunt trauma. The median Injury Severity Score was 25 (16 –34). Eighteen percent of the patients developed MOF, 18% died, and 24% developed MOF and died. The mean initial (first value on the first day) α-MSH concentration was significantly lower than in controls (15.9 pg/mL ± 7.6 pg/mL vs. 26.1 pg/mL ± 7.4pg/mL, p = 0.0008) and did not change significantly during the 5-day study period. On univariate and adjusted multivariate analyses, initial α-MSH concentrations did not predict either MOF or mortality. CONCLUSIONS: The current study is the first to document significantly decreased α-MSH concentrations in critically injured trauma patients as compared with controls. Furthermore, α-MSH concentrations remained so throughout the study period.